Biomass activated carbon properties through activation method for supercapacitor - a mini-review / Madhiyah Yahaya Bermakai, Nor Farahin Jafri and Norha Abdul Hadi - Yahaya Bermakai, Madhiyah; Jafri, Nor Farahin; Abdul Hadi, Norha (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Recently, the development of activated carbon electrodes from agricultural waste biomass for application in carbon-based electrode of supercapacitor is increasing. The use of agricultural waste biomass as a precursor for the production of activated carbon become popular because it is economical, easily available and also beneficial in reducing waste disposal problem in agricultural industries. In this review, the biomass material for activated carbon using various activators is presented. The effects of activating methods which is physical and chemical activation on the properties of activated carbons are reviewed. Carbonaceous materials with high surface area, which is above 1000 m2g-1 and good porosity with total pore volume approximately 1.0 cm3g-1 promote fast ion-transport, making them an ideal choice to be used in supercapacitor. Previous study had shown that different types of activation method influence significantly on the properties of activated carbon produced. Producing a high porosity and high surface area of activated carbon are essentials to fabricate a high quality of supercapacitor. With proper treatment, it is found that many agriculture wastes have high potential and carry good properties as an electrode in supercapacitor.